2015
DOI: 10.1002/pbc.25463
|View full text |Cite
|
Sign up to set email alerts
|

Preventive antibiotics in pediatric patients with acute myeloid leukemia (AML)

Abstract: Background Treatment of acute myeloid leukemia (AML) comes with a significant risk of life‐threatening infection during periods of prolonged severe neutropenia. We studied the impact of preventive intravenous (IV) antibiotic administration at onset of absolute neutropenia on the incidence and outcome of life‐threatening infections during treatment of childhood AML. Procedures This is a retrospective study on pediatric patients (aged 0–18 years) consecutively diagnosed with de novo AML and treated at a single i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 18 publications
(35 reference statements)
1
25
1
3
Order By: Relevance
“…In order to prevent neutropenic sepsis, and VGS sepsis in particular, different approaches in terms of antibiotic prophylaxis have been considered [11, 23]. The Oregon Health and Science University retrospectively studied the use of iv vancomycin and ceftazidime and later iv cefepime mono and could demonstrate low rates of infection and VGS sepsis, in particular [24]. At St. Jude Children’s Research center, a prophylactic regimen combining iv vancomycin with oral ciprofloxacin or a cephalosporin has been administered to pediatric AML patients in neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent neutropenic sepsis, and VGS sepsis in particular, different approaches in terms of antibiotic prophylaxis have been considered [11, 23]. The Oregon Health and Science University retrospectively studied the use of iv vancomycin and ceftazidime and later iv cefepime mono and could demonstrate low rates of infection and VGS sepsis, in particular [24]. At St. Jude Children’s Research center, a prophylactic regimen combining iv vancomycin with oral ciprofloxacin or a cephalosporin has been administered to pediatric AML patients in neutropenia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a single institution study showed that prophylactic intravenous antibiotic use during neutropenia was associated with no deaths from infections in pediatric AML patients, but this study also did not directly compare cohorts of patients who received prophylaxis and those who did not. [18]…”
Section: Discussionmentioning
confidence: 99%
“…В настоящее время недостаточно рассматривать только АР как единственную основную проблему, связанную с устойчивостью бактерий, в том числе УПМ, к антибио-тикам [27,28]. Бактериальная инфекция, в особенности вызванная грамнегативными УПМ, нередко непосред-ственно угрожает жизни иммунокомпрометированных пациентов с онкологическими заболеваниями [29,30], однако возможное значение персистерных форм в раз-витии УПМ-инфекции остается пока неизвестным, хотя и вполне обоснованно предполагается [31,32]. В насто-ящее время для этой категории больных, особенно среди детей с онкогематологическими заболеваниями, ставится вопрос не только о правильном и своевременном назна-чении антибиотиков [29,30], но и о целесообразности их применения у отдельных пациентов [28].…”
Section: Discussionunclassified
“…Бактериальная инфекция, в особенности вызванная грамнегативными УПМ, нередко непосред-ственно угрожает жизни иммунокомпрометированных пациентов с онкологическими заболеваниями [29,30], однако возможное значение персистерных форм в раз-витии УПМ-инфекции остается пока неизвестным, хотя и вполне обоснованно предполагается [31,32]. В насто-ящее время для этой категории больных, особенно среди детей с онкогематологическими заболеваниями, ставится вопрос не только о правильном и своевременном назна-чении антибиотиков [29,30], но и о целесообразности их применения у отдельных пациентов [28]. Предполагается, что, несмотря на небольшое количество персистеров в популяции бактерий, их последующее накопление по-тенциально может служить резервуаром инфекции после антибиотикотерапии [33][34][35].…”
Section: Discussionunclassified